Gaya Kepengarangan dalam Puisi Populer Indonesia Berdasarkan Sistem Tanda dan Makna Simbolik - Sovia Wulandari; Liza Septa Wilyanti; Anggi Triandana (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The sign system in poetry is an element that builds poetry. Therefore, each poem displays a different style based on the use of symbolic signs. The purpose of this study is to classify the style of authorship in Indonesian popular poetry based on the system of signs and symbolic meanings used by the author. The approach used to analyze the sign system and the symbolic meaning is a semiotic approach. The style of authorship is analyzed based on a stylistic approach. The method used for data analysis is a qualitative-descriptive method. The results showed that the sign system and symbolic meaning in Indonesian popular poems are signs in the form of symbols. The symbols are divided into four, namely symbols in the form of phonemes, words, sentences, and typography. Based on the system of signs and symbolic meanings, the styles of authorship in Indonesian popular poems are classified, namely: 1) styles that rely on phonemes; 2) word-based style; 3) sentence-based style, and 4) style that relies on typography. The conclusion of this research is that there are four sign systems and four types of writing styles. The style of authorship based on the sign system in the form of phonemes, words, sentences, and typography is the level of the sign system that is the center of meaning in a poem.